The Association Between Sociodemographic Factors and The Return Visits Among Pediatric Tuberculosis Patients at Primary Health Care Facilities in DKI Jakarta Province - Putu Erma Pradnyani; Syarif Rahman Hasibuan; Gede Wirabuana Putra (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2026)
Indonesia is the second-largest contributor to global tuberculosis (TB) casesin 2023. Tuberculosis in children can significantly affect a child's nutritional status and growth and development. This study aimed to examine the association between sociodemographic factors and return visits among pediatric TB patients to primary health care facilities in DKI Jakarta Province. This study utilized secondary data obtained from the Indonesian Health Insurance Agency (BPJS Kesehatan) for the years 2021-2022. The sample consisted of BPJS Kesehatan participants aged ≤18 years who had been diagnosed with TB (ICD-10 A15, A16, A17, A18, and A19), had active BPJS Kesehatan membership status, and had visited an primary health care in 2021. After weighting, the sample size was 6,729 participants. The independent variables were age group, place of residence, gender, participant segmentation, and BPJS Kesehatan class. The primary outcome variable was return to visit (identifying whether patients who visited a primary healthcare facility in 2021 returned to the primary care in 2022 for a follow-up or control visit). Analysis using logistic regression. The results showed that of the 6,729 pediatric patients, 5,648 (83.9%) still had TB in 2022. Statistical analysis revealed that sociodemographic factors age category, gender, place of residence, and BPJS care class significantly correlate with return visit childhood TB in Jakarta. The results of this study are expected to serve as a basis for developing policies for the prevention and early detection of TB in children within families and communities.